Pengaruh Audit Tenure dan Independensi Auditor Terhadap Kualitas Audit pada Laporan Keuangan PT TPS FOOD TBK 2017 - Muhammad Agustian Sakha; Wildan Zaky; Riska Oktavianti; Heni Nur Anggraeni; Herlina Manurung (Jurnal Akuntan Publik, 2023)
The research method was carried out using literature studies from secondary data, data is the result of searches through media such as the internet, books, and other articles that are appropriate to the case to be discussed. In this research, a case study of PT Tiga Pilar Sejahtera Food Tbk was carried out. In the case of financial reports audited by KAP Amir Abadi Jusuf, Aryanto, Mawar & Partners, the engagement period between the company and KAP has been in place for a long time. It is suspected that PT Tiga Pilar Sejahtera Food Tbk (AISA) overstated the 2017 financial report. The main point of this problem was discovered after the new management at PT Tiga Pilar Sejahtera Food Tbk asked for further investigation into the 2017 financial report. Based on the results of investigations carried out by CNCB journalists, it was found that the engagement period had been since 2004. Based on Government Regulation Number 20 of 2015 concerning Public Accounting Practices, it was clear that it had exceeded 5 years. Audit tenure is questioned in this case, how independent an auditor is in completing his duties to carry out an audit of financial statements if the engagement period exceeds the applicable provisions. The independence of an auditor must be emphasized further so that audit quality can be trusted more by stakeholders.